Co-fermented yellow wine lees by Bacillus subtilis and Enterococcus faecium regulates growth performance and gut microbiota in finishing pigs - Zhang, Yu; Wang, Cheng; Su, Weifa; Jiang, Zipeng; He, Huan; Gong, Tao; Kai, Lixia; Xu, Huangen; Wang, Yizhen; Lu, Zeqing (Frontiers in Microbiology, 2022)
Fermented feeds (FF) are widely used to increase feed utilization and improve pig performance. Based on the preparation of co-fermented yellow wine lees using Bacillus subtilis and Enterococcus faecalis, The purpose of this study was to investigate the effects of co-fermented feed on growth performance, meat quality, immune status and gut microbiota of finishing pigs. Seventy-five finishing pigs (89.59 ± 1.30 kg) were randomized to 3 treatments (5 replicates/treatment), basal diet (Control), a basal diet supplemented with 4% fermented feed (4%FMF), and a basal diet supplemented with 8% fermented feed (8%FMF) for 50 days each. Results showed that the FMF group significantly reduced the F/G and increased the average daily weight gain of pigs compared to the CON group. In addition, FMF increased serum IgA, IgM, IL-4 and IL-10 levels. Simultaneously, FMF improved the volatile flavor substances of pork, increased the content of flavor amino acids, and played a positive role in the palatability of pork. In addition, FMF improved the richness of Lactobacillus and Bacillus subtilis in the gut, which correlated with growth performance, serum immune parameters, and meat quality. Furthermore, acetate and butyrate in the feces were improved in the FMF group. Overall, 8%FMF improved the growth performance and immune status in finishing pigs, improved meat quality and regulated the gut microbiota associated with fiber degradation.